Directed ortho Metalation (DoM)-Linked Corriu–Kumada, Negishi, and Suzuki–Miyaura Cross-Coupling Protocols: A Comparative Study - Quesnelle, Claude A.; Snieckus, Victor (Synthesis, 2018)
A systematic study of the widely used, titled name reaction transition-metal-catalyzed cross-coupling reactions with attention to context with the directed ortho metalation (DoM) is reported. In general, the Suzuki–Miyaura and Negishi protocols show greater scope and better yields than the Corriu–Kumada variant, although the latter qualitatively proceeds at fastest rate but has low functional group tolerance. The Negishi process is shown to be useful for substrates with nucleophile and base-sensitive functionality and it is comparable to the Suzuki–Miyaura reaction in efficiency. The link of these cross-coupling reactions to the DoM strategy lends itself to the regioselective construction of diversely substituted aromatics and heteroaromatics.
Keywords: Suzuki–Miyaura coupling; Negishi coupling; Kumada coupling; comparison